Research and theory of Corporate Political Activity (CPA): a bibliometric analysis - Beal Partyka, Raul; Lana, Jeferson; Amado Bahia Gama, Marina; Marcon, Rosilene (Revista de Negócios, 2019)
Corporate Political Activity (CPA) are ways in which companies use themselves to try to influence regulatory policies and environments in their interests. This article aims to highlight the importance of the CPA in the context of companies seeking political alignment to develop their strategies. Through a bibliometric analysis, based on 180 articles, it was possible to verify that the United States, Canada, and China have effectively advanced research on the subject. Due to the need to develop further studies on the subject in Brazil, suggestions for future research are presented, because it is understood that, through a greater number of studies related to CPAs, we will understand the reasons and forms by which companies are involved with the regulatory environment. The article contributes to clarify the field of corporate political activities, their classification, and implications, advancing with future needs for the researchers of this community.